Evidence for a long‐lived accommodation/transfer zone beneath the Snake River Plain: A possible influence on Neogene magmatism?. Issue 12 (8th December 2015) - Konstantinou, Alexandros; Miller, Elizabeth
Abstract: Geochronologic data compiled from 12 metamorphic core complexes and their flanking regions outline important differences in tectonic and magmatic histories north and south of the Snake River Plain‐Yellowstone Province (SRP‐Y). Magmatism, crustal flow, metamorphism, and extensional exhumation of core complexes north of the SRP occurred mostly between 55 and 42 Ma as compared to 42–25 Ma south of the SRP, with final exhumation of the southern complexes occurring only during younger Miocene (20–0 Ma) Basin and Range faulting. These significant differences in the timing of events suggest that the now lava‐covered SRP, which is at a high angle to Cordilleran trends, may have at times operated as a steep shear or transfer zone accommodating difference in strain to the north and south. Following previous suggestions, we infer that this proposed accommodation or transfer zone developed above an important lithospheric boundary localized above a tear in the subducting slab (shallower slab angle to the south) used to explain both the locus of Late Cretaceous‐Paleocene magmatism and the different ages and mechanisms of slab reconfiguration and removal north and south of the SRP during the Cenozoic. The details of these different histories help outline the complex evolution of this zone and also suggest that this zone of lithospheric weakness may have subsequently focused Miocene SRP‐Y hot spot magmatism. Key Points: The regional history of the SRP indicates a preexisting tectonic boundary The SRP transfer zone was related to the subduction of the Farallon slab